Complementary approaches to problem solving in healthcare and public health: implementation science and human-centered design. Issue 5 (28th September 2020) - Chen, Elizabeth; Neta, Gila; Roberts, Megan C
Abstract : Complementary approaches to problem solving in healthcare and public health: implementation science and human-centered design": Combining implementation science and human-centered design approaches is novel and these complementary approaches can be applied together to optimize the integration of evidence-based practices within clinical and public health settings.